OPPORTUNITIES OF ENDOSCOPIC RETROGRADE STENTING OF THE BILE DUCTS IN MALIGNANT TUMORS OF THE PANCREATOBILIARY ZONE, COMPLICATED BY OBSTRUCTIVE JAUNDICE - S. A. Budzinsky; S. G. S.G. Shapovalyants; E. D. Fedorov; A. G. Mylnikov; A. G. Pankov; P. L. Chernyakevich (Неотложная медицинская помощь, 2016)
Purpose. In the last 10 years in the treatment of acute jaundice, developed on a background of malignant tumors of the pancreatobiliary zone (PBZ), more preferred method is endoscopic retrograde biliary drainage.Material and methods. From January 2007 to July 2012 in the clinic of hospital surgery N. 2 PRNMU endoscopic biliary stenting was performed in 441 patients. Of these, 324 (73.5%) stenting fell to 234 patients with a tumor of the extrahepatic bile ducts. The diagnostic program included ultrasonography, computed tomography, endoscopic ultrasonography and endoscopic retrograde cholangiopancreaticography.Results. Installing of bilioduodenal stent in 223 patients (95.3%) was generated after the pre-endoscopic papillosphincterotomy (EPST). The adequacy of the biliary drainage after produced in the required amount of biliary stent placement was achieved in all patients. In 46 cases, execute the biliary tract prosthesis failed. Complications of endoscopic interventions presented with acute pancreatitis, cholangitis, bleeding from the area of EPST, perforated duodenal wall and migration of the stent were in 19 cases (5?9%). Postoperative mortality was 3?8%. 7 patients (3%) died after the endoscopic decompression of the biliary tract. After stenting in all patients with jaundice it was resolved or significantly reduced. In 185 of them (79%) was the definitive guide endoscopic treatment because of severity of tumor process. In cases of jaundice reccurence endoscopic stent recanalizing or replacement were performed. In the remaining cases (21%) patients after the resolution of jaundice decompressive surgical intervention were done.Conclusion. The method of endoscopic retrograde biliary drainage allows you to prepare patients with obstructive jaundice for surgical intervention, including the radical. The frequency of complications after endoscopic retrograde operations on the major duodenal papilla for acute jaundice blastomatous origin did not differ from that after the standard retrograde interventions and was 6%.